On the implementation and improvement of automatic EEG spike detection algorithm - Misiūnas, Andrius Vytautas Misiukas; Meškauskas, Tadas; Juozapavičius, Algimantas (Lietuvos matematikos rinkinys, 2015)
The algorithm of automatic EEG spike detection and its implementation is described in this article. The algorithm implemented is based on mathematical morphological filters which distinguishes background brain activity from EEG spikes. The implementation of the algorithm is system independent, it can be deployed on both personal computers and clusters with MPI parallel computing support.